2020
DOI: 10.21873/anticanres.14416
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Geriatric Nutritional Risk Index in Patients With Synchronous Colorectal Liver Metastasis

Abstract: Background/Aim: The Geriatric Nutritional Risk Index (GNRI) is a prognostic indicator for several cancers; however, the association between the GNRI and colorectal liver metastasis (CRLM) remains unknown. Patients and Methods: Eighty patients who underwent hepatectomy for synchronous CRLM were divided into two groups based on the GNRI. Results: The preoperative CA19-9 levels were significantly higher in the low (GNRI ≤98; n=30) than the normal GNRI group (GNRI >98; n=50). Patients in the low GNRI group had poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
(18 reference statements)
3
17
0
Order By: Relevance
“…Interestingly, the GNRI is also a prognostic factor for patients with colorectal liver metastasis. 34 However, similar results have been found in other malignancies. 35 In general, GNRI can predict the survival, postoperative complications, tumour metastasis, and recurrence of elderly patients with cancer.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, the GNRI is also a prognostic factor for patients with colorectal liver metastasis. 34 However, similar results have been found in other malignancies. 35 In general, GNRI can predict the survival, postoperative complications, tumour metastasis, and recurrence of elderly patients with cancer.…”
Section: Discussionsupporting
confidence: 79%
“…'s study suggested that the preoperative GNRI can be used as an identifier for the potential morbidity and mortality of elderly CRC patients. Interestingly, the GNRI is also a prognostic factor for patients with colorectal liver metastasis 34 . However, similar results have been found in other malignancies 35 .…”
Section: Discussionsupporting
confidence: 73%
“…Seven of the studies lacked relevant outcomes. Therefore, our meta-analysis included nine studies involving 2,153 patients [ 10 , 12 , 14 , 19 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were from Japan, and two studies were from China. Two studies reported GC [ 19 , 22 ], three studies reported ESCC [ 14 , 20 , 21 ], two studies reported CRC [ 10 , 12 ], one study reported colorectal liver metastasis (CRLM) [ 24 ], and one study reported pancreatic ductal adenocarcinoma (PDAC). In addition, four studies reported postoperative complications, eight studies reported OS, two studies reported RFS, and two studies reported DFS and CSS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent reports revealed that GNRI is associated with prognosis for cancer patients. Iguchi et al reported that GNRI is helpful as an independent prognostic factor for patients with colorectal liver metastasis [ 29 ]. Hirahara et al also showed that GNRI is significantly associated with overall survival and cancer specific survival in elderly gastric cancer patients, and GNRI is an independent predictor of overall survival [ 30 ].…”
Section: Discussionmentioning
confidence: 99%